2012
DOI: 10.3758/s13423-012-0272-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling working memory: An interference model of complex span

Abstract: This article introduces a new computational model for the complex-span task, the most popular task for studying working memory. SOB-CS is a two-layer neural network that associates distributed item representations with distributed, overlapping position markers. Memory capacity limits are explained by interference from a superposition of associations. Concurrent processing interferes with memory through involuntary encoding of distractors. Free time in-between distractors is used to remove irrelevant representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
539
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 346 publications
(592 citation statements)
references
References 160 publications
(266 reference statements)
44
539
1
8
Order By: Relevance
“…The mechanism by which unbinding takes place is identical to that which accomplishes response suppression during recall. Oberauer, Lewandowsky, et al (2012) showed that with the inclusion of this unbinding process, SOB-CS produces the linear effect of cognitive load on memory performance.…”
Section: Cognitive Load (B1)mentioning
confidence: 99%
See 4 more Smart Citations
“…The mechanism by which unbinding takes place is identical to that which accomplishes response suppression during recall. Oberauer, Lewandowsky, et al (2012) showed that with the inclusion of this unbinding process, SOB-CS produces the linear effect of cognitive load on memory performance.…”
Section: Cognitive Load (B1)mentioning
confidence: 99%
“…The two forms of interference most favoured by the evidence --interference by confusion of items, and interference from superposition --are implemented in a computational model of WM, the SOB-CS model (Oberauer, Lewandowsky, et al, 2012), which allows us to determine what predictions the mechanisms imply when operating jointly.…”
Section: Interferencementioning
confidence: 99%
See 3 more Smart Citations